BiP Proteins from Symbiodiniaceae: A “Shocking” Story - Estefanía Morales-Ruiz; Tania Islas-Flores; Marco A. Villanueva (Microorganisms)
More than four decades ago, the discovery of a companion protein of immunoglobulins in myeloma cells and soon after, of their ability to associate with heavy chains, made the term immunoglobulin binding protein (BiP) emerge, prompting a tremendous amount of effort to understand their versatile cellular functions. BiPs belong to the heat shock protein (Hsp) 70 family and are crucial for protein folding and cellular stress responses. While extensively studied in model organisms such as Chlamydomonas, their roles in dinoflagellates, especially in photosynthetic Symbiodiniaceae, remain largely underexplored. Given the importance of Symbiodiniaceae-cnidarian symbiosis, critical for the sustaining of coral reef ecosystems, understanding the contribution of Hsps to stress resilience is essential; however, most studies have focused on Hsps in general but none on BiPs. Moreover, despite the critical role of light in the physiology of these organisms, research on light effects on BiPs from Symbiodiniaceae has also been limited. This review synthesizes the current knowledge from the literature and sequence data, which reveals a high degree of BiP conservation at the gene, protein, and structural levels in Symbiodiniaceae and other dinoflagellates. Additionally, we show the existence of a potential link between circadian clocks and BiP regulation, which would add another level of regulatory complexity. The evolutionary relationship among dinoflagellates overall suggests conserved functions and regulatory mechanisms, albeit expecting confirmation by experimental validation. Finally, our analysis also highlights the significant knowledge gap and underscores the need for further studies focusing on gene and protein regulation, promoter architecture, and structural conservation of Symbiodiniaceae and dinoglagellate BiPs in general. These will deepen our understanding of the role of BiPs in the Symbiodiniaceae-cnidarian interactions and dinoflagellate physiology.